Menelisik Perilaku Forgiveness bagi Perempuan Korban Kekerasan Dalam Rumah Tangga - Elviana, Elviana; Syam, Hidayani (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2024)
Domestic violence often occurs and women are generally the victims. However, this does not always lead to acts of revenge by the victim against the perpetrator, but rather the emergence of forgiveness behavior by the victim towards the perpetrator. This research aims to find out and reveal forgiveness behavior in women who are victims of domestic violence. The approach in this research is descriptive qualitative with a literature study type of research related to forms of domestic violence, forms of forgiveness behavior carried out and factors that cause the emergence of forgiveness behavior for women victims of domestic violence. From the results of the literature study, it was found that there are several types of violence experienced by women in the household, including physical violence, psychological violence, and sexual violence and also neglect. The behavior of forgiveness carried out by women victims of domestic violence consists of various forms including total forgiveness by returning to a good relationship with the perpetrator, serving the perpetrator; forgive but do not live with the perpetrator; and there are also those who do not forgive at all and have the desire to avenge the perpetrator's actions. This forgiveness behavior arises because it is influenced by various factors such as an individual's religiosity, personality, and the presence of children, economic status and also the presence of people or family around them.